The effects of motivational priming on food portion size behavior. Issue 1 (1st January 2016) - Webster, Cynthia; Chakrabarty, Subhra; Kinard, Brian R.
ABSTRACT: This research relied on regulatory focus theory to explore the extent to which the priming of a consumer's goals or motivation toward promotion or prevention significantly affects their food portion size behavior. Two different experiments employing randomized post-test only with control group designs were executed. In Study 1, consumers' motivations were moderately primed; the results supported regulatory focus theory in that a promotion prime led to an increase in food portion size behavior, and a prevention prime caused a decrease in food portion size behavior. In Study 2, consumers' motivations were primed more subtly. When primed subtly or implicitly, regulatory focus theory was supported only for promotion-oriented consumers.